The behaviour of corporate actors: a survey of the empirical literature - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2008)
Much of behavioural research, both in economics and in psychology, is limited in one respect: it tests isolated individuals. In many practically relevant situations, there are discernible actors, but these actors are not individuals. Rather firms, regulatory bodies, associations, countries or international organisations become active. The social problem at hand is best understood if one attributes judgement and decision making to higher level aggregates of individuals. Which elements from the rich body of behavioural evidence transfer to these corporate actors? Are there other deviations from the predictions of the rational choice model, not present or studied in individuals? This paper surveys the empirical literature from experimental economics, psychology, sociology and law. While some building blocks, like the behaviour of managers and of ad hoc groups, are relatively well understood, our knowledge about the effects of more elaborate internal structure on the dealings of corporate actors with the outer world is still relatively limited.
Keywords: C92; 330; Behaviour; Firms; Organizations; associations; groups; Unternehmen; Organisationsverhalten; Gruppenentscheidung; Welt